Intelligent public transport guide system for Kuala Lumpur - Ayu, Media Anugerah; Jamil, Mohd Faisal (IIUM Press, 2011)

(untitled)
Intelligent Public Transport Guide System for Kuala Lumpur is a system which aims to help the user to plan their journey to specific places in Kuala Lumpur using public transport. The system is also developed as a website that helps locals and tourists to get to know about Kuala Lumpur city and its attractive places. Hopefully that with the existence of this system, the rate of using public transport among public will increase and reduce the congestion problem exist in Kuala Lumpur. The Journey Planner system is a web based system which allow any user to access it anywhere as long as internet connection is there. This will be convenient to the user and they are able to plan their journey before they actually arrive at public transport station. This system is build using PHP and MySQL database. One of the advantages of this system is that it will integrate different types of public transports together to provide a more complete journey route to the users. Besides journey planning, the system provides information of major destinations in Kuala Lumpur and different types of public transport available in Kuala Lumpur.